Shear behaviour of geopolymer-concrete beams transversely reinforced with continuous rectangular GFRP composite spirals. (1st March 2018) - Maranan, G.B.; Manalo, A.C.; Benmokrane, B.; Karunasena, W.; Mendis, P.; Nguyen, T.Q.
Abstract: This paper investigated the shear behaviour of geopolymer-concrete beams reinforced with continuous glass-fibre-reinforced polymer (GFRP) composite spirals. Eight large-scale beams were designed, cast, and tested up to failure to evaluate the effects of the spiral pitch, web-reinforcement configuration, shear-span-to-effective-depth ratio, and longitudinal-reinforcement ratio. The results showed that the spirally-reinforced beam produced shear strength and deflection capacities that were 20% and 120% higher than the conventionally reinforced beam. These enhancements could be attributed to the inclination of the spiral links being approximately normal to the shear cracking direction and the continuous nature of the spirals that effectively resisted the shear stresses and controlled the shear cracks and deformations. The beam with closely spaced spirals exhibited better shear performance than those with widely spaced spirals owing to the enhancement of the shear contribution of the confined concrete core, longitudinal-reinforcement dowel action, and aggregate interlock. The modified Zararis analytical model and the ACI 318 strut-and-tie model produced the most accurate predictions of the shear strength of the slender and short beams, respectively. It can be concluded, therefore, that the continuous GFRP spirals are viable alternative to the commonly used closed GFRP stirrups.